Comunidades como subcategoria no contexto das políticas públicas ambientais no Brasil - João Vicente Costa Lima (Universidade do Vale do Rio dos Sinos (UNISINOS), 2015)
The present work discusses the (des)connections between the environmental public policies and the data from the visible cultural diversity in an enriched spectrum of traditional communities. From a sociological point of view, we criticize the environmental approaches bias that minimized the human dimension in its models. It is important to state a difference from the cultural studies in order to demonstrate that the natural spaces are socially and culturally constituted and, in this way, the notion of sustainability is inseparable from the cultural dynamics. The analysis discusses the overlap among Market, Society and State and the connections they establish with the dimension of nature conservation in a multiplicity of contemporary socio-environmental settings.